Shear strength dataset of hollow concrete block masonry with different mortar beddingMendeley Data - Milena Mesa-Lavista; Paola Romo-Letechipía; José Álvarez-Pérez; Ricardo González-Alcorta; Jorge H. Chávez-Gómez; G. Fajardo-San Miguel (Data in Brief)
Masonry is a construction material composed of units (blocks or bricks) joined with mortar. It is one of the most widely used materials in construction resisting both vertical and horizontal forces in single and multi-family housing buildings. A correct union between the units and the mortar (interface) is essential, as is determining the resistance from the applied loads. There is a divergence in how the mortar is bedded in the construction of masonry walls. In some countries, such as Canada and Australia, regulations require that the mortar be placed in face shell bedding when hollow blocks are used. However, in countries like Mexico, regulations establish that it be placed in the net area, and construction practices often differ. Much research has been conducted to study the compressive behavior of mortar bedding in masonry of hollow concrete blocks. However, fewer studies have focused on shear behavior. This paper presents the dataset of experimental laboratory tests on wallettes built with hollow concrete blocks. Two methods of mortar bedding were employed: over the net area and the lateral face. The values obtained can be used to compare the shear strength in hollow concrete block masonry and the shear failure. Additionally, they can be useful for calibrating numerical models.